2013
DOI: 10.5603/cj.a2017.0105
|View full text |Cite
|
Sign up to set email alerts
|

Inducible miR-145 expression by HIF-1α protects cardiomyocytes against apoptosis via regulating SGK1 in simulated myocardial infarction hypoxic microenvironment

Abstract: (Cardiol J 2018; 25, 2: 268-278)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Previous studies confirm that the Pi3K/aKT pathway can activate HiF-1α, thus playing an important role in cell growth and cell survival (22,30). research has shown that the activation of the Pi3K/aKT/HiF-1α pathway mediates protection against lung i/r injury (28), and the upregulation and activation of the Pi3K/aKT/HiF-1α pathway is involved in the protective effects of micrornas on cardiomyocytes (37). Troxerutin preconditioning has been shown to protect against Mi/r injury by inhibiting apoptosis and activating the Pi3K/aKT pathway (34).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies confirm that the Pi3K/aKT pathway can activate HiF-1α, thus playing an important role in cell growth and cell survival (22,30). research has shown that the activation of the Pi3K/aKT/HiF-1α pathway mediates protection against lung i/r injury (28), and the upregulation and activation of the Pi3K/aKT/HiF-1α pathway is involved in the protective effects of micrornas on cardiomyocytes (37). Troxerutin preconditioning has been shown to protect against Mi/r injury by inhibiting apoptosis and activating the Pi3K/aKT pathway (34).…”
Section: Discussionmentioning
confidence: 85%
“…In gastric cancer, miR-145 could inhibit the tumor cell migration by targeting MYO6 [28]. In neuropathic pain, miR-145 could ameliorate this perplex by inhibiting inflammatory responses through the mTOR signaling pathway [35]. In the present study, we predicted the target gene of miR-145, and proved that FOXO1 was a target gene in VECs.…”
Section: Discussionmentioning
confidence: 52%
“…Cardiac remodeling, characterized by reduced heart function and excessive interstitial collagen, 3 is a common pathological phenomenon among post‐MI patients. miR‐145 is widely known as an anticancer noncoding RNA, 29 and previous studies have shown that it has cardioprotective effects, inhibiting inflammation and apoptosis 9‐11 and accelerating autophagy 30 in cardiomyocytes. Moreover, overexpression of miR‐145 in the MI heart significantly improved cardiac function and decreased the size of the MI area 11,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on the myocardial cells, where upregulation of miR-145 delayed the development of cardiovascular diseases. Sun and coworkers [9][10][11] demonstrated that miR-145 inhibited hypoxia-induced cardiomyocyte injury by targeting programmed cell death 4. Recently, Huang et al 12 found that miR-145 could ameliorate cardiac fibrosis, and the long-noncoding RNA metastasis-associated lung adenocarcinoma transcript 1, which function as a miR-145 sponge and promoted cardiac fibrosis via regulation of transforming growth factor-β1.…”
Section: Introductionmentioning
confidence: 99%